2014
DOI: 10.1016/j.beth.2014.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Exposing Clinicians to Exposure: A Randomized Controlled Dissemination Trial of Exposure Therapy for Anxiety Disorders

Abstract: Objective The present study evaluated three technology-based methods of training mental health providers in exposure therapy (ET) for anxiety disorders. Training methods were designed to address common barriers to the dissemination of ET, including limited access to training, negative clinician attitudes toward ET, and lack of support during and following training. Method Clinicians naïve to ET (N=181, Mage = 37.4, 71.3% female, 72.1% Caucasian) were randomly assigned to: 1) an interactive, multimedia online… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
87
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(95 citation statements)
references
References 36 publications
7
87
0
1
Order By: Relevance
“…Indeed, all three training methods resulted in significant and comparable gains in clinical use and proficiency, with clinicians increasing to moderate levels on both outcomes. Consistent with the emerging consensus in the field, these results suggest that relatively brief didactic trainings may need to be augmented with supervision or consultation for clinicians, perhaps particularly those with no prior experience in a given EST, to reach a high level of competence and to further increase knowledge gains (e.g., Beidas et al, 2012;Harned et al, 2014;Herschell et al, 2010;Miller, Yahne, Moyers, Martinez & Pirritano, 2004;Sholomskas et al, 2005). Given that lack of available supervision is a primary barrier to implementation cited by clinicians in this study and others (e.g., Dimeff et al, 2009), more work is clearly needed to develop effective methods of making supervision and consultation more widely available.…”
Section: Discussionsupporting
confidence: 75%
“…Indeed, all three training methods resulted in significant and comparable gains in clinical use and proficiency, with clinicians increasing to moderate levels on both outcomes. Consistent with the emerging consensus in the field, these results suggest that relatively brief didactic trainings may need to be augmented with supervision or consultation for clinicians, perhaps particularly those with no prior experience in a given EST, to reach a high level of competence and to further increase knowledge gains (e.g., Beidas et al, 2012;Harned et al, 2014;Herschell et al, 2010;Miller, Yahne, Moyers, Martinez & Pirritano, 2004;Sholomskas et al, 2005). Given that lack of available supervision is a primary barrier to implementation cited by clinicians in this study and others (e.g., Dimeff et al, 2009), more work is clearly needed to develop effective methods of making supervision and consultation more widely available.…”
Section: Discussionsupporting
confidence: 75%
“…Our findings are also in line with research in clinical supervision of EBPs demonstrating that engaging in role plays with expert supervisors results in better use of EBPs than discussions during supervision (Bearman et al, 2013). Supplementing online training with motivational interviewing and regular group calls with a supervisor following training has also shown to increase clinical proficiency and knowledge of course content (Harned et al, 2014). Taken together, there is a growing body of research pointing to the critical utility of role play skill practice and expert involvement after didactic training in order to maintain high fidelity to CBT and other EBPs.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in several studies it has been shown that training resulted in fewer beliefs about the potential harmful effects of exposure therapy (Deacon et al, 2013; Harned et al, 2014; Ruzek et al, 2016; van den Berg et al, 2016) or EMDR (D. Farrell & Keenan, 2013), but it is unclear whether these more positive beliefs indeed translate to more (adequate) use of these treatments (Gray, Elhai, & Schmidt, 2007). In addition, following on from this training, therapists may need support or supervision so that the need for exposure to their own feared situations, i.e.…”
Section: Introductionmentioning
confidence: 99%